PERAN MAJELIS TA`LIM SHOLAWAT TERHADAP PARTISIPASI KEAGAMAAN REMAJA ISLAM DI ERA MEDIA SOSIAL - Freni Mega Hidayah; Ikhwan Aziz Q; Rina Mida Hayati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The development of digital technology in the era of social media has shifted the pattern of religious interaction among adolescents in Hargomulyo Village from physical activities to virtual spaces, resulting in a drastic decline in participation in Majelis Ta'lim activities. The focus of this research problem is to analyze the strategic role of the Majelis Ta'lim Sholawat Mahabbatir Rasul in increasing adolescent religious engagement amidst the massive digitalization. The important steps or stages of this research use a qualitative approach with a phenomenological method through participatory observation, in-depth interviews with administrators and adolescents, and documentation studies analyzed inductively using an interactive model. The research findings reveal that the Majelis Ta'lim plays a crucial role as a facilitator of spiritual development through routine sholawat, a forum for strengthening Islamic brotherhood, and an inclusive religious discussion space for the congregation. Although successful in providing inner peace and moral improvement, the effectiveness of da'wah outreach to the younger generation is still hampered by conventional methods and the minimal optimization of digital platforms as a means of propagation. Field data confirms the dominance of older participants, while adolescents tend to be distracted by online entertainment content. The main conclusion emphasizes that the Majelis Ta'lim is obliged to innovate da'wah strategies that are more participatory, adaptive, and information technology-based. This transformation is crucial for strengthening religious digital literacy and building collective religious awareness that is relevant to the characteristics of today's youth in a sustainable manner to maintain the moral existence of the Indonesian nation.